Neighbourhood watch: mechanisms and moral implications - Lub, Vasco (The British journal of criminology, 2018)
Drawing from ethnographic fieldwork in the Netherlands, this article illustrates how neighbourhood watch schemes contribute to lower crime levels, advancing criminological theory on community crime prevention. The plausibility of assumed neighbourhoods watch mechanisms varies according to the social status of the area in which a scheme operates. The article further shows how this form of community crime prevention is not without moral implications. Exacerbated by the increasing popularity of digital surveillance techniques and securitization sentiments among active residents, stigmatization, ethnic profiling and excessive social control are real issues, particularly in relatively safe suburban areas. Some principles are proposed to limit excessive responses of watch groups.